The Problems of Students' mathematics Learning at Grade 5 SDN 14 Koto Anau in the post Pandemic Era - Guswandi, Erick (The Future of Education Journal, 2023)
The aims of this study were (1) to find out the results of interviews with teachers and students regarding problems in learning mathematics, (2) to find out the results of learning observations related to understanding mathematical concepts. The location of this research is at SDN 14 Koto Anau, Lembang Jaya District, Solok Regency, West Sumatra Indonesia. The research was conducted in the even semester of January 2022. The subjects of this study were class teachers and students in class V SDN 14 Koto Anau, a total of 17 students. Data collection techniques using interviews with teachers and students, and observation. After getting the data, it is done with naturalistic qualitative analysis techniques. Based on the results of interviews and observations it is known that there are many problems and students' understanding of concepts is still low